Determination of Diagnostic Accuracy of TIRADS Scoring on Ultrasonography in the Management of Thyroid Nodules - Ghafoor, Ayesha; Mir, Alia; Saleem, Ramisa; Rubab, Nayyar (Indus Journal of Bioscience Research, 2025)
Objectives: To determine the diagnostic accuracy of ultrasonography-based TIRADS scoring on differentiating benign and malignant thyroid nodules, taking histopathological findings as the gold standard. Study design: Cross-sectional validation study. Place and duration of study: Department of Diagnostic Radiology, Islamabad Medical Complex, NESCOM Hospital, Islamabad, from November 2024 to April 2025. Methodology: A total of 330 patients, belonging to age range 18 to 65 years, presenting with palpable thyroid nodules were enrolled in this study. Ultrasonography was performed and nodules were scored according to the ACR-TIRADS 2017 criteria. Nodules were then classified as TR1–TR2 (benign) or TR3–TR5 (malignant). All patients then underwent ultrasound-guided FNAC or diagnostic lobectomy and classified as benign or malignant. Diagnostic indices including sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and overall accuracy were calculated taking histopathological finding as gold standard. Results: Mean age of patients was 40.12±11 (with age range 25 to 65 years) comprising of higher proportion of female patients (67%). Malignancy prevalence was 39.4% (130/330 patients). The diagnostic accuracy of ACR-TIRADS for identifying malignant thyroid nodules was 60%. Evaluation of ACR-TIRADS using ultrasonography demonstrated high sensitivity (92.7%) and negative predictive value (89.5%). However, specificity was relatively lower at 38.4%, with a positive predictive value of 49.6%. Conclusion: ACR-TIRADS demonstrates excellent sensitivity and negative predictive value, making it highly effective and reliable method for excluding thyroid malignancy and reducing unnecessary invasive procedures in these patients. However, its low specificity results in considerable false-positive rates thereby requiring careful clinical interpretation.